(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: To assess the microleakage of metallic copings lutied using two different luting cements that are readily accessible. Materials and Methods: Two sets of 40 abutment analogue replicas were machined. The fabrication of nickel chromium copings included the evaluation of the marginal gap using an optical microscope and the luting of the gap using zinc oxide non-eugenol and zinc phosphate cement. Cemented specimens were immersed in a 0.5% aqueous solution of basic fuchsin solution for 24 hours after thermocycling to allow dye penetration. Microleakage scores were calculated and sections of copings were longitudinally analyzed. Analytical Statistics Kruskal -Wallis analysis of variance (ANOVA) and the Chi-Square test were also used. Result: As a result, Zinc Phosphate Cement had the lowest mean microleakage score and Zinc Oxide Non Eugenol had the highest. P <0.05 indicates that the study's findings were statistically significant. Conclusions: It was discovered that all cements showed some degree of microleakage within the parameters of the investigation. The difference in the mean microleakage scores of zinc phosphate and zinc oxide non-eugenol cements was found to be negligible, indicating that the microleakage in both cements is comparable.